Electrophysiologic Findings and Long‐Term Outcomes in Patients Undergoing Third or More Catheter Ablation Procedures for Atrial Fibrillation. (28th January 2015) - LIN, DAVID; SANTANGELI, PASQUALE; ZADO, ERICA S.; BALA, RUPA; HUTCHINSON, MATHEW D.; RILEY, MICHAEL P.; FRANKEL, DAVID S.; GARCIA, FERMIN; DIXIT, SANJAY; CALLANS, DAVID J.; MARCHLINSKI, FRANCIS E.
Outcomes After Third or More Catheter Ablation for Atrial Fibrillation: Introduction: Pulmonary vein (PV) status, arrhythmia sources, and outcomes with ≥3 ablation procedures have not been characterized. Methods and Results: All patients with ≥3 procedures were included and underwent antral reisolation of reconnected PVs and ablation of non‐PV triggers. Of 2, 886 patients who underwent PVI, 181 (6%) had more than 2 ablation procedures (3 procedures in 146 and ≥4 procedures in 35). In 12 patients, the clinical arrhythmia was other than AF. Of the remaining 169 patients, 69 (41%) had 4 reconnected PVs, 27 (16%) had 3, 31 (18%) had 2, and 29 (17%) had 1. Only 13 (8%) had all PVs still isolated. Provocative techniques in 127 patients initiated PV triggers in 92 patients, including AF or PV atrial tachycardia in 64 (50%), and reproducible PV APDs in 28 (22%). Thirty‐six (20%) had a new non‐PV trigger targeted. At a mean of 36 months (12–119 months) after last procedure, 63 patients (47%) had no AF off antiarrhythmic drugs (AAD); 28 (21%) had no AF with AAD; and 18 (13%) had rare AF with good symptom control; 26 patients (19%) had recurrent AF. Conclusions: At time of third or greater AF ablation, PV reconnection is the rule (92%) and PV triggers initiating AF can be demonstrated. Following repeat PVI and targeting non‐PV triggers, 81% of patients had clinical AF control. Our findings suggest that PV reisolation and attempts to identify and eliminate non‐PV triggers are effective and support the role of multiple repeat procedures for AF recurrence.